Glycaemic and sensory impacts of using rare sugars in reformulated sucrose-containing foods - Smith, Alison (2024)
Non-communicable diseases including obesity, type 2 diabetes, cardiovascular disease and non-alcoholic fatty liver disease present a large and growing global health burden. These conditions share common risk factors, and the primary recommended action to reduce risk is dietary and lifestyle change, including reducing intake of energy and free sugars.